The assessment of acoustical performance of mosques in Shah Alam / Abdul Hakim Abdullah and Muhammad Amir Jazli Mohd Razali - Abdullah, Abdul Hakim; Mohd Razali, Muhammad Amir Jazli (Universiti Teknologi MARA, Perak, 2023)
A mosque is a place where Muslims conduct activities such as praying and listening to talks. Therefore, it is important for a mosque to have great acoustics quality as it influences the worshipper's experience when praying or listening to Imam's preaches. The acoustical evaluation in the mosque is rarely conducted and, in most cases, the development of good acoustic quality in the mosque is never considered at an early stage of design. In the present investigation, two large-volume mosques in Shah Alam were investigated: Section 7 Mosque (MS7) and Sultan Salahuddin Abdul Aziz Mosque (MSA). The objective of this study is to evaluate the acoustical characteristics of the mosque and its quality level. In addition, the speech intelligibility performance of each mosque was also determined using Speech Transmission Index (STI) and Rapid Transmission Index (RASTI). The experimental work found that the reverberation time of MSA has attained recommended values of reverberation time for that given size and volume while MS7 has slightly higher. The speech level attainment of both mosques is sufficient for worshippers to hear comfortably, but the background noise is high. Nevertheless, the signal-to-noise ratio (S/N ratio) indicates that both mosques have been able to obtain more than 15 dB(A) for improved speech intelligibility. The STI and RASTI prediction shows that MS7 has attained 'fair' and 'bad' ratings. In contrast, 'poor' and 'bad' ratings are achieved in the MSA.